Polypropylene mesh and conchal cartilage composite graft: a novel technique for orbital floor reconstruction - Venkataramani, Nithya; Kumaran, Satish; Sachidananda, Ravi; Vasista, Srividya Rao; Navaneetham, Romir; Navaneetham, Anuradha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Fractures of the orbital floor can occur as a part of maxillofacial trauma and be associated with prolapse of orbital contents into maxillary sinus. It may be associated with entrapment signs mandating surgical repair of the orbital floor. Aim of the study was to study the role of a composite graft in the repair of orbital floor fractures in a tertiary care center. Methods: Retrospective chart review of 16 patients who underwent orbital floor repair in a tertiary care center was undertaken. All patients underwent surgical repair with a composite graft made of cartilage and polypropylene mesh by subciliary approach. Results: Post-operatively, none of the patients had restriction of mobility, diplopia, or globe asymmetry. Mild entropion was noted in two patients but did not require any intervention. No extrusion of the implant was seen. Conclusions: Conchal cartilage and polypropelene mesh composite graft is a reliable and easily available material for the repair of orbital floor defects in almost all kinds of orbital floor fractures.